2021
DOI: 10.1371/journal.pone.0245065
|View full text |Cite
|
Sign up to set email alerts
|

Timing and causes of neonatal mortality in Tamale Teaching Hospital, Ghana: A retrospective study

Abstract: Neonatal deaths now account for more than two-thirds of all deaths in the first year of life and for about half of all deaths in children under-five years. Sub-Saharan Africa accounts up to 41% of the total burden of neonatal deaths worldwide. Our study aims to describe causes of neonatal mortality and to evaluate predictors of timing of neonatal death at Tamale Teaching Hospital (TTH), Ghana. This retrospective study was conducted at TTH located in Northern Ghana. All neonates who died in the Neonatal Intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
5
19
0
Order By: Relevance
“…Baroni et al [ 7 ] investigated the neonatal mortality rates in Brazil, whereas Liu et al [ 8 ] and Abdul-Mumin et al [ 9 ] investigated the key reasons for neonatal death and preterm birth in China and Ghana. Regional investigations have identified that preterm birth, intrapartum complications and pneumonia (in case of China), and preterm birth complications and birth asphyxia (in case of Ghana) are the leading causes of neonatal deaths [ 8 , 9 ]. On a global scale, the major causes of neonatal death include preterm birth, severe infections and asphyxia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baroni et al [ 7 ] investigated the neonatal mortality rates in Brazil, whereas Liu et al [ 8 ] and Abdul-Mumin et al [ 9 ] investigated the key reasons for neonatal death and preterm birth in China and Ghana. Regional investigations have identified that preterm birth, intrapartum complications and pneumonia (in case of China), and preterm birth complications and birth asphyxia (in case of Ghana) are the leading causes of neonatal deaths [ 8 , 9 ]. On a global scale, the major causes of neonatal death include preterm birth, severe infections and asphyxia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers have mostly considered a single outcome variable; in some cases, two variables were considered to examine the association between maternal obesity with other variables of interest, including miscarriage, stillbirth [ 4 ] and neonatal death [ 8 , 9 ]. In contrast, this research has taken a holistic approach to compare and contrast how maternal obesity is related to pre and post-birth maternal and neonatal risk factors by including multiple outcome variables together.…”
Section: Introductionmentioning
confidence: 99%
“…These changes may be attributed to conjugate vaccination and herd immunity in older children. Our study excluded infants aged <60 days who typically have bacterial meningitis due to different pathogens [17], different clinical presentation [26], and alternative diagnoses such as birth asphyxia [27], and associated higher risk of neurological disability and mortality [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, neonatal deaths reduced from 30 per 1000 live births in 1998 to 25 per 1000 live births in 2017 [6]. There was a descending trend in neonatal mortality over 5year period between 2013 to 2017 [7].…”
Section: Introductionmentioning
confidence: 97%
“…Determinants of neonatal deaths in Ghana include multiple births, household size, parity, contraceptives use, birth weight, and population density [6]. The predictors of early neonatal death for Normal Birth Weight Babies in Tamale Metropolis include gender, being born at Tamale Teaching Hospital and Birth Asphyxia while Low Birth Weight are the place of delivery and Birth Asphyxia [7]. Siakwa et al [4] stated the global three top causes of neonatal deaths as birth asphyxia (41%) infection (29%), preterm (29%) and prematurity and Low Birth Weight (15%).…”
Section: Introductionmentioning
confidence: 99%